Ehrlichiosis in a Recent Liver Transplant Recipient Leading to Multiorgan Failure - Fawwaz Almajali; Catherine Oleary; Taylor Hallcox; Justin Lok; Daniela Hermelin; Alexis Guenette; Mustafa Nazzal (Case Reports in Transplantation)
Ehrlichia infection has a broad spectrum of diseases ranging from asymptomatic to fatal. While Ehrlichia often presents as a mild form of the disease in immunocompetent patients, immunosuppressed patients are at increased risk for a more virulent and potentially fatal infection. Our liver transplant patient presented with fever, persistent headaches, and negative Ehrlichia antibodies. Empiric antibiotic therapy was started and along with knowledge of prior tick infection, doxycycline was added. Subsequent positive PCR and observation of Ehrlichia chaffeensis in peripheral blood smear confirmed the diagnosis. The patient did recover from infection but not before it manifested in hepatic, renal, and pulmonary involvement. Therefore, a high level of suspicion is necessary for early detection and treatment initiation to prevent a devastating progression of the disease in immunosuppressed patients.